THE RELATIONSHIP BETWEEN WORKLOAD AND STRESS ON NURSES DURING THE COVID-19 PANDEMIC IN INTENSIVE CARE UNIT (ICU) OF MERAUKE HOSPITAL - Bekti Sukoco; Frans Manangsang; Endah Purwanti; Renona Delianna L Tobing (International Journal Of Health Science, 2023)
Workload becomes a source of stress if the amount is not proportional to both physical ability and expertise and the time available to nurses. In addition, nurses are faced with the covid-19 pandemic situation which requires them to work longer and more carefully due to the infectious nature of the virus, especially in intensive care rooms. Patient care in the ICU during the pandemic requires nurses to go the extra mile because they are at the forefront of their response. This study will examine the relationship between workload and stress in nurses in the ICU room of Merauke Hospital. The method used is quantitative association with Cross Sectional approach. A total of 40 nurses were designated as research samples with total sampling techniques. The research measuring instrument used questionnaires using univariate data analysis using frequency distribution and bivariate data analysis using rho spearman. The results of the analysis of the relationship between the two variables using the Spearman rho correlations statistical test with the help of the SPSS program showed significant (p) = 0.000 smaller than (α) = 0.05. This means that there is a significant relationship between workload and nurse work stress in the ICU room of Merauke Hospital. With the Spearman correlation coefficient rho (r) = 0.964. This means that it has a strong level of relationship strength and a positive correlation coefficient value so that the relationship is unidirectional. There is a meaningful relationship between workload and nurse work stress in the ICU room of Merauke Hospital. The higher the workload, the higher the nurse's work stress level